Solid electrolyte and preparation method thereof, solid composite electrode, solid battery and equipment
By growing sulfide electrolytes in situ in the inner pores of the oxide electrolyte framework to form a composite solid electrolyte, the problems of low ionic conductivity and poor interface stability when sulfide electrolytes are used in solid-state batteries are solved, and higher ionic conductivity and interface stability are achieved, which improves the application prospects of solid-state batteries.
Patent Information
- Application Number
- CN202510528020.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-06-24
AI Technical Summary
When sulfide electrolyte is used in solid-state batteries, there are problems of low ionic conductivity and poor interface stability, which limits the practical application of solid-state batteries.
The oxide electrolyte skeleton is used as support to form a composite solid electrolyte by growing sulfide electrolyte in situ in the inner channel of the skeleton. This method enhances the application prospects of batteries by improving the ionic conductivity and interface stability of the electrolyte layer.
By reducing the internal impedance of solid electrolytes, promoting multi-dimensional uniform transmission of lithium ions, improving the ionic conductivity and interface stability of the battery, significantly improving the cycling performance and application prospects of solid-state batteries.
Smart Images

Figure CN120199880A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly relates to a solid electrolyte and a preparation method thereof, a solid composite electrode, a solid battery and a device. Background Art
[0002] Liquid batteries are currently the most common lithium-ion batteries, but they have high safety risks due to problems such as the use of flammable liquid electrolytes, leakage and corrosion, and the easy penetration of the separator by negative lithium dendrites. Solid batteries use solid electrolytes that are non-flammable and have good mechanical properties to replace liquid electrolytes, which can effectively reduce the safety risks of lithium-ion batteries.
[0003] Currently, most solid batteries choose sulfide electrolytes with high ionic conductivity and good processing plasticity as their solid electrolytes. However, the composite solid electrolytes in the batteries have problems such as low ionic conductivity of the electrolyte layer and poor interfacial stability, which greatly restricts the practical application of solid batteries using sulfide electrolytes. Summary of the Invention
[0004] One of the purposes of the present invention is to provide a solid electrolyte and a preparation method thereof, a solid composite electrode, a solid battery and a device to solve the problem of poor applicability of sulfide electrolytes in solid batteries.
[0005] In order to achieve the above purpose, the technical scheme adopted by the present invention is as follows:
[0006] A solid electrolyte includes: an oxide electrolyte framework and a sulfide electrolyte. The oxide electrolyte framework has interconnected pores inside, and the sulfide electrolyte adheres to the pores.
[0007] Further, the pore diameter of the pores is 0.1 - 80 μm, and / or the thickness of the solid electrolyte is 20 - 100 μm.
[0008] Further, in the solid electrolyte, the mass ratio of the oxide electrolyte framework in the solid electrolyte is 2% - 30%.
[0009] A preparation method of a solid electrolyte includes:
[0010] Mixing an oxide electrolyte with a pore-forming agent and pressing them into a solid mixture;
[0011] Calcining the solid mixture to obtain a three-dimensional oxide electrolyte framework, and the oxide electrolyte framework has interconnected pores inside;
[0012] Let a sulfide electrolyte precursor solution grow in-situ on the pore channels to obtain a sulfide electrolyte attached to the pore channels, and use an oxide electrolyte framework with a sulfide electrolyte attached to the internal pore channels as the prepared solid electrolyte.
[0013] Further, letting the sulfide electrolyte precursor solution grow in-situ on the pore channels includes:
[0014] Mix the sulfide electrolyte precursor solution with the oxide electrolyte framework by heating, and calcine the mixture.
[0015] Further, the temperature for calcining the mixture is 300 - 500 °C, and the calcination duration is 2 - 5 h.
[0016] Further, the sulfide electrolyte precursor solution is obtained by mixing Li2S, P2S5, and substance M in a preset molar ratio after adding a solvent. The substance M is at least one of P2O5, LiO2, SiO2, Fe2O3, ZrO2, ZnO, TiO2, La2O3, Nb2O5, GeO2, LiI, LiBr, and LiCl, and the solvent is selected from one of benzene, toluene, p-xylene, hexane, dodecane, cyclohexane, anisole, and liquid alkyl esters.
[0017] Further, the preset molar ratio is x:y:(100 - x - y), where 0 < x < 40 and 0 < y < 40.
[0018] Further, the mass ratio of the sulfide electrolyte precursor solution to the oxide electrolyte framework is 1:5 - 50;
[0019] and / or, the mass ratio of the pore-forming agent to the oxide electrolyte is 1:1 - 5;
[0020] and / or, the pore-forming agent is at least one of graphite, ammonium fluoride, ammonium carbonate, ammonium bicarbonate, ammonium chloride, urea, charcoal, starch, and cellulose;
[0021] and / or, the oxide electrolyte is at least one of LLZO, LLTO, LZO, and LLZTO;
[0022] and / or, the pressing pressure is 20 - 80 MPa and the pressing duration is 5 - 30 minutes.
[0023] Further, the calcination process of the solid mixture includes two calcinations. The temperature of the first calcination is 400 - 600 °C and the duration is 2 - 5 h, and the temperature of the second calcination is 900 - 1200 °C and the duration is 1 - 3 h.
[0024] A solid composite electrode includes a positive electrode sheet and an electrolyte layer, and the electrolyte layer is formed by pressing the solid electrolyte described in any one of the above or the solid electrolyte prepared by the method described in any one of the above on one side of the positive electrode sheet.
[0025] A solid-state battery includes the solid electrolyte described in any one of the above or the solid composite electrode described in any one of the above.
[0026] An electrical device includes the above solid-state battery.
[0027] The beneficial effects of the present invention: The solid electrolyte includes an oxide electrolyte framework and a sulfide electrolyte attached to the pores inside the framework. On the one hand, the oxide electrolyte has a high ionic conductivity and has a low influence on the loss of the ionic conductivity of the sulfide electrolyte. At the same time, by means of the pores of the oxide electrolyte framework, the sulfide electrolyte is in-situ grown, which is beneficial to reducing the internal impedance of the solid electrolyte and promoting the multi-dimensional uniform transmission of lithium ions. On the other hand, the oxide electrolyte framework can minimize the direct contact between the sulfide electrolyte in its internal pores and the positive and negative electrode materials, reduce the production of by-products such as low-conductivity ions, thereby reducing the negative impact on the battery performance caused by the unnecessary reaction of the sulfide electrolyte, ensuring that the solid-state battery has a high ionic conductivity and interfacial stability, and improving the application prospect of the solid-state battery. Description of the Drawings
[0028] Figure 1 It is a schematic structural diagram of a solid electrolyte provided by an exemplary embodiment of the present invention;
[0029] Figure 2 It is a schematic flow diagram of a preparation method of a solid electrolyte provided by an exemplary embodiment of the present invention;
[0030] Figure 3 It is a schematic structural diagram of a solid composite electrode provided by an exemplary embodiment of the present invention.
[0031] Through the above drawings, the clear embodiments of the present invention have been shown, and there will be more detailed descriptions hereinafter. These drawings and textual descriptions are not intended to limit the scope of the inventive concept in any way, but to illustrate the concept of the present invention to those skilled in the art by referring to specific embodiments. Detailed Embodiments
[0032] The embodiments of the present invention will be described below with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, rather than for limiting the protection scope of the present invention.
[0033] It should be noted that the diagrams provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner. Therefore, only the components related to the present invention are shown in the diagrams, rather than being drawn according to the number, shape, and size of the components in actual implementation. The type, quantity, and proportion of each component in actual implementation can be arbitrarily changed, and the layout type of its components may also be more complex.
[0034] Exemplary embodiments will be described in detail herein, which are illustrated in the accompanying drawings. When the following description refers to the accompanying drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present invention as detailed in the appended claims.
[0035] The term "comprising", "including" or any other variant thereof is intended to cover a non-exclusive inclusion, such that a process, method, product or device comprising a series of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, product or device. Without further limitation, there is no exclusion of additional identical or equivalent elements in the process, method, product or device comprising the said elements. For example, if the terms first, second, etc. are used to denote names, they do not denote any specific order.
[0036] The quality of the relevant components mentioned in the specification of the embodiments of the present invention not only can refer to the specific content of each component, but also can represent the proportional relationship of the quality between each component. Therefore, as long as the content of the relevant components in the specification of the embodiments of the present invention is enlarged or reduced in proportion, it is within the scope disclosed in the specification of the embodiments of the present invention. Specifically, the quality in the specification of the embodiments of the present invention can be mass units well-known in the chemical field such as μg, mg, g, etc.
[0037] Liquid batteries are the most common lithium-ion batteries on the market at present. However, due to problems such as the use of flammable liquid electrolytes, leakage and corrosion, and the easy penetration of the separator by lithium dendrites at the negative electrode, there are high safety risks. Moreover, various means such as strengthening battery safety management and optimizing the components of the electrolyte cannot fundamentally solve the problem. Solid-state batteries use solid electrolytes that are non-flammable and have good mechanical properties to replace liquid electrolytes, which can not only completely eliminate such safety risks, but also improve the energy density and service life of the battery, and are considered to be the most promising next-generation power batteries.
[0038] Among many solid-state battery systems, sulfide electrolytes have become the focus of research for electrolyte layers and electrode electrolytes due to their good ionic conductivity and processing plasticity. However, in practical applications, after using sulfide electrolytes in batteries, the ionic conductivity is much lower than the ideal situation, and the interfacial stability is also poor, resulting in the quality of solid-state batteries not meeting expectations, seriously restricting the practical application and development prospects of solid-state batteries.
[0039] Through research, it is found in the present invention that the reason for the above problems is that in solid-state batteries, sulfide electrolytes are prone to interface contact with the positive and negative electrode materials in the electrodes and lithium metal, and the electrochemical window of sulfide electrolytes is relatively narrow. After contacting these materials, they are prone to decomposition to produce by-products with low conductivity ions, which in turn has an adverse impact on the ionic conductivity of the electrolyte layer and interfacial stability. Based on this, a technical concept is proposed to use materials with stable chemical properties and high ionic conductivity to isolate sulfide electrolytes as much as possible, avoid direct contact between sulfide electrolytes and other easily reactive materials in solid-state batteries, improve ionic conductivity and interfacial stability, and thus improve the applicability of solid-state batteries.
[0040] Based on the technical concept of the present invention, a solid electrolyte and its preparation method, a solid composite electrode, a solid-state battery and a device are provided.
[0041] The above-mentioned application scenarios are only partial examples, and those skilled in the art can expand the application according to specific needs and scenarios. The embodiments of the present invention do not make specific limitations on this.
[0042] In one embodiment, a solid electrolyte is provided. The solid electrolyte includes: an oxide electrolyte framework and a sulfide electrolyte. The oxide electrolyte framework has interconnected pores inside, and the sulfide electrolyte is attached to the pores.
[0043] Optionally, the pore diameter of the pores is 0.1~80μm.
[0044] Optionally, the thickness of the solid electrolyte is 20~100μm.
[0045] Optionally, the mass percentage of the oxide electrolyte framework in the solid electrolyte is 2% - 30%. The mass percentage of the sulfide electrolyte in the solid electrolyte is 70 - 98%. In the solid electrolyte, when the mass percentage of the oxide electrolyte framework is 2%, the mass percentage of the sulfide electrolyte is 98%. When the mass percentage of the oxide electrolyte framework is 30%, the mass percentage of the sulfide electrolyte is 70%.
[0046] Optionally, the oxide electrolyte serving as the framework is selected from at least one of LLZO, LLTO, LZO, and LLZTO.
[0047] Among them, LLZO, LLTO, LZO, and LLZTO are all abbreviations of solid electrolyte materials. LLZO is lithium lanthanum zirconium oxide, with the chemical formula Li7La3Zr2O 12 . LLTO is lithium lanthanum titanium oxide, with the chemical formula Li 0.33 La 0.56 TiO3. LZO is lanthanum zirconium oxide, with the chemical formula La2Zr2O7. LLZTO is lithium lanthanum zirconium tantalum oxide, with the chemical formula Li 6.4 La3Zr 1.4 Ta 0.6 O 12 .
[0048] Optionally, the sulfide electrolyte is selected from at least one of vitreous sulfide, crystalline sulfide, and ceramic sulfide.
[0049] In the embodiments of the present invention, the sulfide electrolyte in the pores of the oxide electrolyte framework can be in-situ grown on the pores using preparation materials such as a sulfide electrolyte precursor solution. In-situ growth can refer to completely infiltrating the sulfide electrolyte precursor solution into the pores of the oxide electrolyte framework and in-situ growing the sulfide electrolyte on the pores by calcination.
[0050] In the embodiments of the present invention, in-situ growing the sulfide electrolyte by means of the pores in the oxide electrolyte framework is beneficial to reducing the internal impedance of the solid electrolyte and promoting the multi-dimensional uniform transport of lithium ions, thereby improving the conductivity.
[0051] Figure 1 FIG. is a schematic structural diagram of a solid electrolyte provided for an exemplary embodiment of the present invention. As Figure 1As shown, the oxide electrolyte framework can have numerous uniformly distributed and cross-linked pores, and the sulfide electrolyte adheres to the pores. The oxide electrolyte framework can protect the sulfide electrolyte inside. When this solid electrolyte is used in a solid-state battery, it is mainly the oxide electrolyte framework that contacts materials such as the positive electrode sheet and the negative electrode sheet in the solid-state battery. On the one hand, the oxide electrolyte has a high ionic conductivity and has a low impact on the loss of the ionic conductivity of the sulfide electrolyte. On the other hand, the oxide electrolyte framework can minimize the direct contact between the sulfide electrolyte in its internal pores and the positive and negative electrode materials, reduce the production of by-products such as low-conductivity ions, thereby reducing the negative impact on the battery performance caused by unnecessary reactions of the sulfide electrolyte, ensuring that the solid-state battery has a high ionic conductivity and interface stability, and improving the application prospect of the solid-state battery.
[0052] In some possible implementation manners, the oxide electrolyte can be used as a raw material, and the oxide electrolyte framework can be obtained through processes such as pressure calcination. This method is simple to operate and has low cost. When combined with a sulfide electrolyte with good flexibility, the overall is highly dense, which can make the solid electrolyte have good mechanical strength and structural stability. Using this solid electrolyte as the electrolyte layer of the solid-state battery can effectively prevent the penetration of negative lithium dendrites, and can also better withstand internal and external stress changes during the battery cycling process, which has an obvious effect on improving the cycling performance of the battery.
[0053] Figure 2 It is a schematic flow chart of a method for preparing a solid electrolyte provided by an exemplary embodiment of the present invention. As Figure 2 shown, the preparation method can include:
[0054] Step S201, mixing the oxide electrolyte and the pore-forming agent and then pressing them into a solid mixture.
[0055] Exemplarily, the oxide electrolyte powder and the pore-forming agent can be uniformly mixed, and the mixture powder can be pressed into a thin film cake-like solid mixture under a certain pressure.
[0056] Optionally, the oxide electrolyte is at least one of LLZO, LLTO, LZO, and LLZTO.
[0057] Optionally, the pore-forming agent is at least one of graphite, ammonium fluoride, ammonium carbonate, ammonium bicarbonate, ammonium chloride, urea, charcoal, starch, and cellulose.
[0058] Optionally, the mass ratio of the pore-forming agent to the oxide electrolyte is 1:1 to 5. The amount of the pore-forming agent used is related to the pore size and distribution of the pores.
[0059] Optionally, the pressing pressure can be 20 to 80 MPa, and the pressing duration can be 5 to 30 minutes.
[0060] Step S202, calcining the solid mixture to obtain a three-dimensional oxide electrolyte skeleton.
[0061] Among them, the oxide electrolyte skeleton has mutually cross-linked pores.
[0062] For example, the calcination process of the solid mixture may include two calcinations, the first calcination temperature is 400-600° C. and the duration is 2-5 hours, and the second calcination temperature is 900-1200° C. and the duration is 1-3 hours.
[0063] The first calcination at 400-600 degrees for 2-5 hours can fully decompose the pore former to form abundant pores. The second calcination at 900-1200 degrees for 1-3 hours can further strengthen the original porous structure to obtain a complete and stable three-dimensional porous skeleton, providing space for the subsequent in-situ growth of sulfide electrolytes. High-temperature calcination at at least 900 degrees can strengthen the structure of the oxide electrolyte skeleton, prevent the skeleton from being severely deformed or even damaged after contact and collision with other materials in the solid-state battery, and ensure battery performance.
[0064] Step S203, allowing the sulfide electrolyte precursor solution to grow in situ on the pores to obtain the sulfide electrolyte attached to the pores, and using the oxide electrolyte skeleton with the sulfide electrolyte attached to the internal pores as the prepared solid electrolyte.
[0065] The in-situ growth may refer to completely permeating the sulfide electrolyte precursor solution into the pores of the oxide electrolyte skeleton and in-situ growing the sulfide electrolyte on the pores by calcination.
[0066] In an embodiment of the present invention, the sulfide electrolyte precursor solution may be obtained by mixing Li2S, P2S5 and M substance according to a preset molar ratio and then adding a solvent.
[0067] For example, three raw materials of Li2S, P2S5 and M substance can be taken according to the required stoichiometric ratio, and a solvent can be added thereto and then ball milled, and a sulfide electrolyte precursor solution can be obtained after sufficient mixing. The ball milling speed can be 100-600 rpm / min, and rpm / min can represent the number of rotations per minute. The ball milling time can be 0.5-6h.
[0068] Optionally, the M substance is at least one of P2O5, LiO2, SiO2, Fe2O3, ZrO2, ZnO, TiO2, La2O3, Nb2O5, GeO2, LiI, LiBr and LiCl.
[0069] Optionally, the solvent is selected from one of benzene, toluene, p-xylene, hexane, dodecane, cyclohexane, anisole, and liquid alkyl esters.
[0070] Optionally, the preset molar ratio is x:y:(100 - x - y), where 0 < x < 40 and 0 < y < 40.
[0071] Optionally, the mass ratio of the sulfide electrolyte precursor solution to the oxide electrolyte framework is 1:5 to 50.
[0072] By the method in the above embodiments, sulfide electrolytes attached to the pores can be generated in the pores inside the oxide electrolyte framework, so as to combine the advantages of the three-dimensional conduction framework of the oxide electrolyte and the close packing of the in-situ growth of the sulfide electrolyte to improve the ionic conductivity of the electrolyte layer. In a solid-state battery, it is more conducive to achieving a uniform distribution of the lithium-ion flux at the interface between the electrode and the electrolyte layer. On the other hand, the stable oxide framework can effectively isolate and protect the electrode pole piece and improve the mechanical strength of the electrolyte layer.
[0073] In one embodiment, in-situ growth of the sulfide electrolyte precursor solution on the pores includes:
[0074] Mix the sulfide electrolyte precursor solution with the oxide electrolyte framework by heating, and calcine the mixed material.
[0075] Among them, the temperature for calcining the mixed material can be 300 - 500 °C, and the calcination duration can be 2 - 5 h.
[0076] Exemplarily, the sulfide electrolyte precursor solution obtained in the above steps can be continuously and slowly dropped along the thickness direction of the oxide electrolyte framework while setting heating to volatilize the solvent, and finally a densified solid electrolyte can be obtained through calcination.
[0077] In the above embodiments, continuously and slowly dropping the sulfide electrolyte precursor solution on the oxide electrolyte framework and synchronously setting heating conditions to accelerate the evaporation of the solvent can ensure that the raw material components can fully penetrate into all pores as much as possible. Then, during the calcination process, a dense sulfide electrolyte grows in-situ in the pores to completely fill the internal pores, greatly increasing the contact area between the oxide electrolyte framework and the sulfide electrolyte, reducing the grain boundary impedance of lithium-ion transfer inside the electrolyte layer, and thus improving the ionic conductivity of the electrolyte layer. In addition, while playing a rigid support role, the oxide electrolyte framework can effectively prevent the direct contact between the sulfide electrolyte and the positive electrode active material, improving the interface stability.
[0078] In one embodiment, a solid composite electrode is provided. The composite electrode includes a positive electrode plate and an electrolyte layer. The electrolyte layer is formed by pressing the solid electrolyte in the above embodiment onto one side of the positive electrode plate.
[0079] Optionally, the thickness of the positive electrode sheet is greater than 100 μm.
[0080] Figure 3 The schematic diagram of the structure of a solid composite electrode provided by an exemplary embodiment of the present invention. Figure 3 As shown, the positive electrode sheet may include a positive electrode current collector and a supported positive electrode active material layer.
[0081] In one embodiment, a method for preparing a solid composite electrode is provided, which may include: a first step of preparing a positive electrode plate; a second step of preparing a solid electrolyte; and a third step of preparing the positive electrode plate and the solid electrolyte into a solid composite electrode.
[0082] The second step of preparing the solid electrolyte may refer to the preparation method of the solid electrolyte in the above embodiment.
[0083] In the first step, the process of preparing the positive electrode sheet may include: mixing the active material, sulfide electrolyte, conductive agent, and binder in proportion and grinding them thoroughly, then adding a solvent to fully dissolve and stir them, and then coating and drying the stirred slurry on the positive electrode collector to obtain a solid positive electrode sheet.
[0084] Optionally, the positive electrode current collector is any one of plain aluminum foil, carbon-coated aluminum foil, nickel foil and stainless steel foil, and has a thickness of 10-20 μm.
[0085] Optionally, the active material is selected from at least one of a ternary positive electrode material, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide and lithium nickel oxide.
[0086] Optionally, the sulfide electrolyte is selected from at least one of glassy sulfide, crystalline sulfide and ceramic sulfide.
[0087] Optionally, the conductive agent is selected from at least one of vapor grown carbon fiber, super-P Li, super-C 65, acetylene black and Ketjen black.
[0088] Optionally, the binder is selected from at least one of hydrogenated styrene-butadiene block copolymer (SEBS), polyisobutylene (PIB), poly(vinylidene fluoride-co-hexafluoropropylene) copolymer (PVDF-HFP), poly(vinylidene fluoride-co-hexafluoropropylene-tetrafluoroethylene) copolymer (PVDF-HFP-TFE), polyamide (PAN), ethylene acrylate copolymer (AEM) and derivatives thereof.
[0089] Optionally, the solvent is any one of benzene, toluene, p-xylene, hexane, dodecane, cyclohexane, anisole, and liquid alkyl esters.
[0090] Optionally, the grinding can be a ball milling operation, with a ball milling speed of 100 - 500 rpm / min and a ball milling time of 0.5 - 3 h.
[0091] Optionally, the stirring speed is 300 - 1000 rpm / min and the stirring time is 0.5 - 5 h.
[0092] In the third step, the process of preparing the positive electrode sheet and the solid electrolyte into a solid composite electrode may include: using roll transfer printing or isostatic transfer printing to composite the solid electrolyte onto the active material layer side of the solid positive electrode sheet to obtain the solid composite electrode.
[0093] In the above embodiments, through roll transfer printing or isostatic transfer printing, not only can the solid composite electrode be made more dense under a short-term high-pressure environment, but also the components on both sides of the contact interface are more likely to be embedded into the pore structures of each other. At the same time, under heating conditions, the binder in the electrode will turn into a low-viscosity fluid state to further enhance the interface bonding ability, which helps to reduce the interface impedance of lithium-ion transfer and improve the interface stability.
[0094] The above solid composite electrode has the following beneficial effects:
[0095] (1) The electrolyte layer in the solid composite electrode is supported by a three-dimensional porous oxide electrolyte skeleton. Different from the conventional polymer three-dimensional structure, the oxide electrolyte has a higher ionic conductivity than the polymer, so the influence on the loss of ionic conductivity of the sulfide electrolyte is lower. Then, by in-situ growth, the sulfide electrolyte is calcined and deposited in the internal pores of the skeleton. According to the size of the pores, the sulfide electrolyte that closely adheres to the skeleton can be freely grown, realizing the maximum utilization of the internal space and dense packing, effectively reducing the interface impedance of the electrolyte layer, enabling lithium ions to be transported multi-dimensionally through the interconnected three-dimensional porous structure. Therefore, the electrolyte layer exhibits excellent ionic conductivity and a more uniform lithium-ion flux distribution at the electrolyte layer and electrode interface, effectively improving the capacity performance and cycling performance of the battery.
[0096] (2) The rigid and stable oxide electrolyte skeleton in the electrolyte layer protects the sulfide electrolyte as a whole inside the frame, avoiding direct contact between the sulfide electrolyte and the positive and negative electrode active materials, and significantly improving the interface stability. In addition, the rigid oxide electrolyte skeleton is prepared by a pressure calcination process, which is simple to operate and low in cost. It is then compounded with a sulfide electrolyte with good flexibility, and the overall structure is highly dense, which can make the electrolyte layer have good mechanical strength and structural stability, effectively preventing the penetration of negative electrode lithium dendrites. At the same time, it can better withstand internal and external stress changes during the battery cycle, which has a significant effect on improving the battery's cycle performance.
[0097] (3) The internal structure of the solid composite electrode obtained by hot roller transfer or isostatic pressing transfer is more compact. At the same time, the component structure embedded in each other at the interface between the electrode and the electrolyte layer can further increase the contact area. At the same time, the low-viscosity flow binder in the heated state will penetrate into the interface pores to further enhance the interface binding energy, which helps to reduce the interface impedance of lithium ion transfer and improve the interface stability.
[0098] The solid composite electrode provided by the present invention can be applied to solid-state batteries, effectively reducing the ion transfer impedance at the interface between the electrolyte layer and the positive electrode sheet and inside the electrolyte layer and improving the interface stability, so that the battery exhibits better capacity utilization and cycle performance.
[0099] Based on this, a solid-state battery is provided, which may include the solid-state electrolyte or solid-state composite electrode in the above embodiment. In some other possible implementations, the solid-state battery may also include the solid-state electrolyte in the above embodiment and other types of positive and negative electrode materials.
[0100] In one embodiment, an electric device is also provided. The electric device includes the above-mentioned solid-state battery and can provide electric energy for devices such as automobiles or computers.
[0101] To further demonstrate the beneficial effects of the present invention, some specific examples are provided below for illustration.
[0102] <Example 1>
[0103] A solid composite electrode, the specific preparation method is as follows:
[0104] (S1) Preparation of traditional solid-state positive electrode: NCM811, Li6PS5Cl, VGCF and SEBS are mixed in proportion and fully ground, then anisole is added to fully dissolve and stir, and then the stirred slurry is coated and dried on a 12um carbon-coated aluminum foil to obtain a solid-state positive electrode.
[0105] The grinding speed is 300 rpm / min and the grinding time is 1 h.
[0106] The stirring speed is 500 rpm / min and the time is 2 h.
[0107] (S2) Preparation of electrolyte layer:
[0108] (a) 1 g LLZO powder was uniformly mixed with 1 g graphite, and then the mixture powder was pressed at 50 MPa for 10 min to obtain a film cake. The cake was first kept at 500 °C for 2 h to decompose the graphite, and then calcined at 1100 °C for 2 h to obtain a three-dimensional porous LLZO electrolyte skeleton.
[0109] The particle size of LLZO electrolyte is 300nm.
[0110] (b) Li2S, P2S5 and P2O5 were added to cyclohexane in a molar ratio of 1:1:3, and then placed in a ball mill and ground at 150 r / min for 3 h to obtain a sulfide electrolyte precursor solution.
[0111] (c) 20 g of the sulfide electrolyte precursor solution obtained in (b) was slowly added dropwise along the thickness direction of 1 g of LLZO skeleton. After heating and drying, the composite solid electrolyte was annealed at 400 °C for 3 h to obtain the electrolyte layer.
[0112] In the obtained electrolyte layer, the mass proportion of the oxide electrolyte skeleton is 6.5%.
[0113] The thickness of the electrolyte layer is 60 μm.
[0114] (S3) Preparation of solid composite electrode: The electrolyte layer was transferred to the active material layer side of the solid positive electrode sheet at a pressure of 8T and 140°C to obtain a solid composite electrode.
[0115] <Example 2>
[0116] A solid composite electrode, the specific preparation method is as follows:
[0117] (S1) Preparation of traditional solid-state positive electrode: NCM811, Li6PS5Cl, VGCF, and PIB were mixed in proportion and fully ground, and then anisole was added to fully dissolve and stir, and then the stirred slurry was coated on a 12um carbon-coated aluminum foil and dried to obtain a solid-state positive electrode. The grinding speed and time, stirring speed and time were the same as those in Example 1.
[0118] (S2) Preparation of electrolyte layer:
[0119] (a) 1 g of LLTO powder was uniformly mixed with 1 g of urea, and then the mixture powder was pressed at 30 MPa for 10 min to obtain a film cake. The cake was first kept at 450 °C for 2 h to decompose urea, and then calcined at 1000 °C for 2 h to obtain a three-dimensional porous LLTO electrolyte skeleton. The particle size of the LLTO electrolyte was 400 nm.
[0120] (b) Three raw materials of Li2S, P2S5, and P2O5 were added to toluene in a molar ratio of 1:2:2, and then placed in a ball mill and ground at a speed of 200 r / min for 3 h to obtain a sulfide electrolyte precursor solution.
[0121] (c) 15 g of the sulfide electrolyte precursor solution obtained in (b) was slowly dropped along the thickness direction of the 1 g LLTO skeleton. After heating and drying, annealing was carried out at 400 °C for 4 h to obtain a composite solid electrolyte as the electrolyte layer.
[0122] In the obtained electrolyte layer, the mass ratio of the oxide electrolyte skeleton was 9.3%.
[0123] The thickness of the electrolyte layer was 75 μm.
[0124] (S3) Preparation of the solid composite electrode: The electrolyte layer was transferred to the active material layer side of the solid positive electrode sheet under a pressure of 8 T and at 140 °C to obtain a solid composite electrode.
[0125] <Example III>
[0126] A solid composite electrode, and the specific preparation method is as follows:
[0127] (S1) Preparation of the traditional solid positive electrode sheet: NCM811, Li6PS5Cl, VGCF, and PIB were mixed in proportion and then sufficiently ground. Subsequently, anisole was added for sufficient dissolution and stirring, and then the stirred slurry was coated and dried on a 12-μm carbon-coated aluminum foil to obtain a solid positive electrode sheet. Among them, the grinding speed and time, and the stirring speed and time were the same as those in Example I.
[0128] (S2) Preparation of the electrolyte layer:
[0129] (a) 2 g of LLZO powder was uniformly mixed with 1 g of ammonium carbonate, and then the mixture powder was pressed at 60 MPa for 20 min to obtain a film cake. The cake was first kept at 400 °C for 2 h to decompose ammonium carbonate, and then calcined at 1100 °C for 3 h to obtain a three-dimensional porous LLZO electrolyte skeleton.
[0130] The particle size of the LLZO electrolyte was 300 nm.
[0131] (b) Li2S, P2S5, and LiCl were added to cyclohexane in a molar ratio of 1:1:3, and then placed in a ball mill and ground at a speed of 150 r / min for 3 h to obtain a sulfide electrolyte precursor solution.
[0132] (c) 40 g of the sulfide electrolyte precursor solution obtained in (b) was slowly dropped along the thickness direction of the 1 g LLZO framework. After heating and drying, annealing was carried out at 400 °C for 3 h to obtain a composite solid electrolyte as the electrolyte layer.
[0133] In the obtained electrolyte layer, the mass ratio of the oxide electrolyte framework is 3.5%.
[0134] The thickness of the electrolyte layer is 46 μm.
[0135] (S3) Preparation of the solid composite electrode: The electrolyte layer was transferred to the active material layer side of the solid positive electrode sheet under a pressure of 8 T and at 140 °C to obtain a solid composite electrode.
[0136] <Comparative Example 1>
[0137] In this comparative example, the solid composite electrode was prepared using only the LLZO electrolyte framework as the electrolyte layer according to the preparation method of Example 1, and the remaining related steps were kept the same.
[0138] <Comparative Example 2>
[0139] This comparative example was carried out according to the preparation method of Example 3, in which the preparation method of the electrolyte layer was changed as follows: First, the sulfide electrolyte precursor solution was prepared, and then directly heated, dried, and annealed without the oxide electrolyte framework to obtain sulfide electrolyte powder, and then the electrolyte layer was obtained by molding under 100 MPa for 0.5 h.
[0140] The solid composite electrodes prepared in the above examples and comparative examples were applied to solid-state batteries. The preparation method of the solid-state battery was as follows: The solid composite electrodes and lithium-indium negative electrode sheets prepared in the above examples and comparative examples were assembled into a mold battery (inner diameter of the inner tank is 10 mm) in a glove box, and the assembly pressure was 1 T. Subsequently, under the conditions of normal temperature 25 °C and 50 MPa, electrochemical performance tests were carried out, and the test voltage range was 1.9~3.7 V. The test results are shown in the following table.
[0141]
[0142] According to the analysis of the above table, it can be seen that the cycling performance of the solid-state batteries fabricated with the solid composite electrodes in Example 1, Example 2, and Example 3 is significantly improved compared to that of the solid-state batteries fabricated with the solid electrolyte in Comparative Example 2. This indicates that the composite solid electrolyte formed by in-situ growth of sulfide electrolyte in the three-dimensional framework of oxide electrolyte has excellent ionic conductivity, and can effectively prevent the serious interfacial side reactions caused by the direct contact between the sulfide electrolyte and the positive and negative electrodes, improve the interfacial stability, and thus has a certain effect on the improvement of the battery cycling performance.
[0143] By comparing the cycling test results of Example 1 and Comparative Example 1, it can be seen that the pure oxide electrolyte framework is too rigid without filling, and it is prone to structural damage after experiencing internal and external stresses, and lithium dendrites are more likely to deposit and penetrate the framework during the cycling process, resulting in short circuits. After in-situ growth of sulfide electrolyte, its flexibility and density are improved, and the structural stability is better, showing better cycling performance.
[0144] In the above embodiments, the descriptions of each embodiment have their own emphases. For the parts not detailed in a certain embodiment, reference can be made to the relevant descriptions of other embodiments. The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as within the scope described in this specification.
[0145] Those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses, or adaptations of the present invention, which follow the general principles of the present invention and include the common general knowledge or conventional technical means in the technical field not disclosed in the present invention. The specification and examples are only regarded as exemplary, and the true scope and spirit of the present invention are pointed out by the following claims.
[0146] The above embodiments are only preferred embodiments given to fully illustrate the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or transformations made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention.
Claims
1. A solid electrolyte, characterized in that include: An oxide electrolyte skeleton and a sulfide electrolyte, wherein the oxide electrolyte skeleton has mutually cross-linked pores inside, and the sulfide electrolyte is attached to the pores.
2. The solid electrolyte according to claim 1, characterized in that The pore size of the pores is 0.1-80 μm, and / or the thickness of the solid electrolyte is 20-100 μm.
3. The solid electrolyte according to claim 1, characterized in that In the solid electrolyte, the mass proportion of the oxide electrolyte skeleton in the solid electrolyte is 2% to 30%.
4. A method for preparing a solid electrolyte, characterized in that: include: mixing the oxide electrolyte with the pore former and pressing the mixture into a solid; The solid mixture is calcined to obtain a three-dimensional oxide electrolyte skeleton, wherein the oxide electrolyte skeleton has mutually cross-linked pores; The sulfide electrolyte precursor solution is allowed to grow in situ on the pores to obtain the sulfide electrolyte attached to the pores, and the oxide electrolyte skeleton with the sulfide electrolyte attached to the internal pores is used as the prepared solid electrolyte.
5. The preparation method according to claim 4, characterized in that: The step of allowing the sulfide electrolyte precursor solution to grow in situ on the pores comprises: The sulfide electrolyte precursor solution and the oxide electrolyte skeleton are heated and mixed, and the mixed material is calcined.
6. The preparation method according to claim 5, characterized in that: The mixed material is calcined at a temperature of 300-500° C. for 2-5 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The sulfide electrolyte precursor solution is obtained by mixing Li2S, P2S5 and M substances according to a preset molar ratio and adding a solvent, wherein the M substance is at least one of P2O5, LiO2, SiO2, Fe2O3, ZrO2, ZnO, TiO2, La2O3, Nb2O5, GeO2, LiI, LiBr and LiCl, and the solvent is selected from one of benzene, toluene, p-xylene, hexane, dodecane, cyclohexane, anisole and liquid alkyl esters.
8. The preparation method according to claim 7, characterized in that: The preset molar ratio is x: y: (100-xy), wherein 0 <x<40,0<y<40。 9. The preparation method according to any one of claims 4 to 6, characterized in that: The mass ratio of the sulfide electrolyte precursor solution to the oxide electrolyte framework is 1:5-50; And / or, the mass ratio of the pore former to the oxide electrolyte is 1:1-5; and / or, the pore-forming agent is at least one of graphite, ammonium fluoride, ammonium carbonate, ammonium bicarbonate, ammonium chloride, urea, charcoal, starch and cellulose; And / or, the oxide electrolyte is at least one of LLZO, LLTO, LZO and LLZTO; And / or, the pressing pressure is 20-80 MPa and the pressing time is 5-30 minutes.
10. The preparation method according to any one of claims 4 to 6, characterized in that: The calcination process of the solid mixture includes two calcinations, the first calcination temperature is 400-600° C. and the duration is 2-5 hours, and the second calcination temperature is 900-1200° C. and the duration is 1-3 hours.
11. A solid composite electrode, characterized in that: It comprises a positive electrode plate and an electrolyte layer, wherein the electrolyte layer is formed by pressing the solid electrolyte as described in any one of claims 1 to 3 or the solid electrolyte prepared by the method as described in any one of claims 4 to 10 on one side of the positive electrode plate.
12. A solid-state battery, characterized in that: It comprises the solid electrolyte according to any one of claims 1 to 3, or the solid composite electrode according to claim 11.
13. An electrical equipment, characterized in that: Comprising the solid-state battery as claimed in claim 12.
Citation Information
Cited By
Electrolyte material for solid-state battery, electrode material and preparation method
CN122118066A
Electrolyte material, electrode material for solid-state battery and preparation method thereof
CN122118066B
